2013
DOI: 10.3109/14767058.2013.850668
|View full text |Cite
|
Sign up to set email alerts
|

The effect of histological chorioamnionitis on the short-term outcome of preterm infants ≤32 weeks: a single-center study

Abstract: Maternal histological CA is an important risk factor for preterm deliveries and associated with serious morbidities such as early onset sepsis, IVH, PDA and increased mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…In human studies, chorioamnionitis has been associated with neonatal death (27,86), early-onset neonatal sepsis (86)(87)(88), intrauterine growth restriction (89), poor neonatal growth (90), neurologic impairment/injury (91,92), intraventricular hemorrhage (86), bronchopulmonary dysplasia (93)(94)(95), patent ductus arteriosus (86,89,93,96), retinopathy of prematurity (89,97,98), cardiovascular abnormalities (99, 100), necrotizing enterocolitis (101,102), and dermatitis (103). However, low gestational age is often a significant contributing factor (104)(105)(106), and therefore, it is difficult to attribute these sequelae solely to chorioamnionitis.…”
Section: Neonatal Sequelae Of Chorioamnionitismentioning
confidence: 99%
“…In human studies, chorioamnionitis has been associated with neonatal death (27,86), early-onset neonatal sepsis (86)(87)(88), intrauterine growth restriction (89), poor neonatal growth (90), neurologic impairment/injury (91,92), intraventricular hemorrhage (86), bronchopulmonary dysplasia (93)(94)(95), patent ductus arteriosus (86,89,93,96), retinopathy of prematurity (89,97,98), cardiovascular abnormalities (99, 100), necrotizing enterocolitis (101,102), and dermatitis (103). However, low gestational age is often a significant contributing factor (104)(105)(106), and therefore, it is difficult to attribute these sequelae solely to chorioamnionitis.…”
Section: Neonatal Sequelae Of Chorioamnionitismentioning
confidence: 99%
“…The current study also identified a trend between maternal inflammatory response increasing RDS and culture positive sepsis, as well as a significant correlation between culture-positive sepsis and subacute or necrotizing acute chorioamnionitis. The relationship between neonatal sepsis and chorioamnionitis has previously been established [4; 33]. …”
Section: Discussionmentioning
confidence: 99%
“…For 39 infants born <32 weeks gestation who were exposed to CA compared to 33 control infants, there was no difference between groups in mental and psychomotor developmental indices. 31 Similarly, a case control study found no difference in performance on the Bayley Scales of Infant Development between the 71 infants exposed and the 259 infants not exposed to CA at 7 months corrected age. 30 …”
Section: Neonatal Outcomesmentioning
confidence: 95%
“…30 For infants <32 weeks gestational age, 145 infants exposed to histologic CA developed clinical criteria consistent with sepsis syndrome significantly more often than 136 infants without CA, 39% vs 24% (p=0.007). 31 …”
Section: Neonatal Outcomesmentioning
confidence: 99%